Phytochemical Screening, Antioxidant and Antifungal Activities of Aconitum chasmanthum Stapf ex Holmes Wild Rhizome Extracts - Shah Rafiq; Nasir Aziz Wagay; Hosam O. Elansary; Mansoor Ahmad Malik; Irshad Ahmad Bhat; Zahoor Ahmad Kaloo; Abdul Hadi; Abed Alataway; Ahmed Z. Dewidar; Ahmed M. El-Sabrout; Kowiyou Yessoufou; Eman A. Mahmoud (MDPI AG, 2022)
Aconitum chasmanthum Stapf ex Holmes, an essential and critically endangered medicinal plant from Kashmir Himalayas, was studied for its antioxidant and antifungal properties. The shade-dried powdered rhizome was extracted sequentially with hexane, ethyl acetate, and methanol. These subsequent fractions were evaluated for total phenolic content (TPC); total flavonoid content (TFC); antioxidant assays, such as 1,1-diphenyl 1-2-picryl-hydrazyl (DPPH); ferric-reducing antioxidant power (FRAP); superoxide radical scavenging (SOR); hydroxyl radical scavenging (OH) and antifungal activity using the poisoned food technique. Highest TPC (5.26 ± 0.01 mg/g) and TFC (2.92 ± 0.04 mg/g) were reported from methanolic extracts. The highest values of radical scavenging activities were also observed in methanolic extracts with IC50 values of 163.71 ± 2.69 μg/mL in DPPH, 173.69 ± 4.91 μg/mL in SOR and 159.64 ± 2.43 μg/mL in OH. The chemical profile of ethyl acetate extract was tested using HR-LCMS. Methanolic extracts also showed a promising inhibition against Aspergillus niger (66.18 ± 1.03), Aspergillus flavus (78.91 ± 1.19) and Penicillium notatum (83.14 ± 0.97) at a 15% culture filtrate concentration with minimum inhibitory concentration (MIC) values of 230 μg/mL, 200 μg/mL and 190 μg/mL, respectively. Overall, the methanolic fractions showed significant biological potential, and its pure isolates might be used to construct a potential new medicinal source.